The detrimental effects of microplastic exposure on kidney function - Jiang, Na; Zheng, Xiya; Zhang, Nan; Cao, Yingjie (Frontiers in Medicine, 2025)
Microplastics (MPs) are plastic particles with a diameter of less than 5 millimeters, primarily originating from the degradation of plastic products (11). In recent years, increasing attention has also been given to the impact of MPs on the health. Important questions have surfaced, including whether MPs can be cleared by the kidneys, whether reduced kidney function affects their clearance, and whether MP accumulation contributes to the progression of kidney diseases. This review explores the effects of MPs on the kidneys and focuses on their accumulation, toxic effects, and potential molecular mechanisms.